Penatalaksanaan Terapi Finger Painting Dan Melipat Kertas Origami Dengan Masalah Gangguan Tumbuh Kembang Pada Anak Down Syndrome - Silvi, Dela Karita; Rahayuningsih, Tutik; Dermawan, Deden (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: Down syndrome is a condition caused by an abnormality in chromosome development. Developmental disorders are delays in individuals during growth that are not in accordance with their age or developmental level. Finger painting is an activity of drawing using fingers directly as a substitute for crayons and colored pencils because this activity can attract children's interest in trying new things in learning to paint or draw. Finger painting activities applied to children are very suitable activities, in addition to being a play tool, to be able to improve children's fine motor skills. By developing fine motor skills, it will improve the coordination of body movements that will link nerves and muscles in more detail. Origami folding activities for children can be useful for learning in geometric mathematical terms, improving children's fine motor skills, children learn about size and shape, learn to follow sequential instructions, develop logical thinking, concentration exercises for children. Objective: to describe the management of finger painting therapy and origami paper folding with developmental disorders in children with Down syndrome. Method: The research design uses qualitative descriptive with a nursing process approach. The sampling technique is purposive sampling. The number of subjects was 2 subjects, namely Down syndrome children who had developmental disorders. Results: Subject assessment data found it difficult to write, paint or fold paper, lack of eye contact, subjects were unable to speak, subject moods changed, appeared to have difficulty writing, painting and folding paper, bender gestalt test II scores 13 - 14. Nursing diagnosis of developmental disorders related to stimulus deficiency. Nursing interventions were finger painting therapy and origami paper folding for 5 consecutive days with a time of 35 - 45 minutes per day. General evaluation of finger painting therapy and origami paper folding was effective for the development of developmental disorders, especially in skills with bender gestalt test II scores 3 - 4. Implementation of finger painting therapy and paper folding was effective for the development of skills in developmental disorders in Down syndrome children. Conclusion: Finger Painting Therapy and Origami Paper Folding are Effective for Developmental Disorder Problems in Down Syndrome Children.